Hybrids Otsu method, Feature region and Mathematical Morphology for Calculating Volume Hemorrhage Brain on CT-Scan Image and 3D Reconstruction - Sumijan Sumijan; Sarifuddin Madenda; Johan Harlan; Eri Prasetya Wibowo (Universitas Ahmad Dahlan, 2017)
Traumatic brain injury is a pathological process of brain tissue that is not degenerative or congenital, but rather due to external mechanical force, which causes physical disorders, cognitive function, and psychosocial. These disorders can be permanent or temporary and accompanied by the loss of or change in level of consciousness. Segmentation techniques for Computed Tomography Scanner (CT scan) of the brain is one of the methods used by the radiologist to detect abnormalities or brain hemorrhage that occurs in the brain. This paper discusses the extraction area of a brain hemorrhage on each image slice CT scan and 3D reconstruction, making it possible to visualize the 3D shape and calculating the volume of a brain hemorrhage. Extraction of brain hemorrhage area is based on a combination of Otsu algorithm, the algorithm Morphological features and algorithms region. For the reconstruction of a 3D brain hemorrhage area of the bleeding area on a 2D slice is done by using a linear interpolation approach.